Gas Detecting Evaluation by Graphitic-based Silicon Carbide Nanosurface doped with Manganese: A Promising Device for Air Pollution Monitoring - Mollaamin, Fatemeh (The Indonesian Chemical Society, Chapter Nusa Tenggara and The University of Mataram, 2024)
Silicon carbide (SiC) as a direct broad bandgap semiconducting material has the potential to bring a considerable developement into optoelectronic and electronic devices. This article aims to investigate Physico-chemical properties of manganese (Mn)–doped graphene-like silicon carbide (SiC) monolayer sheet by the first-principles methods based on the density functional theory (DFT) for scavenging of CO, CO2, NO, NO2 gas molecules. The results recommend that the adsorption of these gas molecules on Mn-embedded SiC sheet monolayer is more energetically desired than that on the pristine ones. Gas molecules of CO, CO2, NO, NO2 have been adsorbed on the Mn site of doped SiC monolayer through the formation of covalent bonds. The assumption of chemical adsorptions has been approved by the projected density of states (PDOS) and charge density difference plots. Charge density difference calculations also indicate that the electronic densities were mainly accumulated on the adsorbate of CO, CO2, NO, NO2 gas molecules. The ability of SiC nanosheet for monitoring of CO, CO2, NO and NO2 is fluctuated by their selectivity and sensitivity through NMR, NQR, IR and HOMO/LUMO approaches which can represent the efficiency of Mn–doped SiC surface as the promising sensors toward air pollution detecting.